Recovering Real-World Reflectance Properties and Shading from HDR Imagery - Haefner, Bjoern; Green, Simon; Oursland, Alan; Andersen, Daniel; Goesele, Michael; Cremers, Daniel; Newcombe, Richard; Whelan, Thomas (Proceedings - 2021 International Conference on 3D Vision, 3DV 2021, 2021)
We propose a method to estimate the bidirectional reflectance distribution function (BRDF) and shading of complete scenes under static illumination given the 3D scene geometry and a corresponding high dynamic range (HDR) video. By splitting the BRDF into its diffuse and non-diffuse parts we solve the estimation of each component separately. For the diffuse component,we sample the incident illumination at each point in the scene using Monte Carlo ray tracing,allowing us to factor the captured surface color into albedo and shading. We then use a novel ray tracing-based optimization strategy to estimate the non-diffuse parameters of the BRDF. In a variety of experiments,we demonstrate that our method efficiently generates realistic copies of the observed scenes.
CRIS-Team Scopus Importer:2023-03-08
Keywords: Albedo; Appearance; BRDF; De lighting; HDR; Reflectance; Shading; Specular; Texture